Quantum mechanics - Peebles, P. J. E. (New Delhi: Prentice-Hall of India Pvt. Ltd., 1992)
To understand quantum mechanics one ought to know the story of how people hit on this highly nonintuitive world picture, in which the physical state of a system is represented by an element in an abstract linear space and its observable properties by operators in the space. To give a flavour of this fascinating discovery of quantum mechanics, this book begins with an introductory presentation of the origins of quantum mechanics in the usual pseudohistorical style of physics. The goal of this introduction is to show how classical physicists could have hit on wave mechanics. The general principles of quantum mechanics are stated next, first in terms of wave mechanics and then in the standard abstract linear space formalism. Measurement theory, essential to practise quantum mechanics by applying it to real physical problems, is discussed in some detail to show how the mathematical theory is to be related to the results of measurement. The book also emphasizes the art of numerical estimates. The remainder of the book presents a selection of the applications of quantum mechanics drawn from perturbation theory, atomic and molecular structure, and scattering theory. The main topic in perturbation theory is the computation of the energy and spontaneous decay rate of the 21 cm hyperfine in atomic hydrogen. The large number of problems presented chapter-wise are physically interesting-some easy, some challenging. This text on quantum mechanics is suitable for advanced undergraduate and postgraduate students in physics.
Index 417-419p.
Keywords: Quantum mechanics; Physics